The contributions of smallholder subsistence agriculture towards rural household food security in Maroteng Village, Limpopo Province - Mashamaite, Kgalema Abbyton (University of Limpopo (Turfloop Campus), 2014)
Smallholder subsistence agriculture is regarded as an approach that can be adopted by poor rural households to meet their food and nutritional requirements. The practice of smallholder subsistence agriculture is a basis upon which poor households can enhance their household food security through increased incomes and food supply, ultimately generating extra income for other household needs. The present study discusses and analyses the importance of smallholder subsistence agriculture as an effective method easily available to households residing in rural areas to access food and incomes for household purposes. Hence, the study seeks to explore and analyses the role of smallholder subsistence agriculture in contributing to household food security in rural areas. Both primary and secondary data have been used to analyze the factors for the purpose of the study. The primary data were collected through a designed survey questionnaire administered to sampled smallholder subsistence farmers in the study area. This study used purposive sampling technique, through a transect walk, to draw households involved in smallholder subsistence agriculture in Maroteng Village. From the total population in the study area, only 100 households were selected for the purposes of the study. Both descriptive and qualitative techniques were used to analyze salient variables of the practice in order to give an insight of the important role the sector can play in addressing poverty, enhancing incomes and creating employment, consequently contributing to household food security in rural areas. The study shows that the participation on smallholder subsistence farming by households in rural areas could have positive impact on food security situations.
Thesis (M.A. Admin. (Development)) -- University of Limpopo, 2014.
Keywords: Smallholder subsistence agriculture; Food security; Subsistence farming -- South Africa -- Limpopo; Food supply -- South Africa -- Limpopo; Food security; Farms, Small -- South Africa -- Limpopo; Agriculture -- Economic aspects -- South Africa -- Limpopo